2021
DOI: 10.3201/eid2701.201043
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Human Metapneumovirus Gene Duplication Variants in Patients with Severe Acute Respiratory Infection, China, 2017–2019

Abstract: We detected human metapneumovirus (HMPV) in 72 (7.1%) of 1,021 patients hospitalized with severe acute respiratory infection in Luohe, China, during 2017–2019. We detected HMPV most frequently in young children and less often in adults. HMPV genotype A2c variants 111 nt and 180 nt duplications predominated, demonstrating their continuing geographic spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 14 publications
(22 reference statements)
6
13
0
Order By: Relevance
“…A similar frequency of hMPV coinfections (14.6%) has been reported in other countries [35]. However, several authors also reported a significantly higher proportion of hMPV coinfections -58 [36] and 63.9% [9]. hMPV infection in Bulgaria had a clear seasonality with the highest frequency of occurrence in winter and spring months, which was consistent with data from other countries with temperate climates [22,27,37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar frequency of hMPV coinfections (14.6%) has been reported in other countries [35]. However, several authors also reported a significantly higher proportion of hMPV coinfections -58 [36] and 63.9% [9]. hMPV infection in Bulgaria had a clear seasonality with the highest frequency of occurrence in winter and spring months, which was consistent with data from other countries with temperate climates [22,27,37].…”
Section: Discussionsupporting
confidence: 87%
“…Based on nucleotide sequence analysis of the F and G genes, hMPV is classified into 2 major genetic groups (A and B), and these are further divided into 4 major genotypes (A1, A2, B1, and B2) and 2 additional genotypes (A2a and A2b) [6]. Recently, 3 novel hMPV subtypes A2b1, A2b2, and A2c have been proposed [8,9]. In a particular season, viruses from these different genotypes can co-circulate within the same region as the predominant genotypes can vary annually.…”
Section: Introductionmentioning
confidence: 99%
“…Because all 8 viruses for which sequences of the G gene could be obtained showed a111-nt duplication in the G gene, it may be considered likely that this variant has been responsible for most infections during the outbreak. This variant was first described in 2016 and has gradually become the dominating strain worldwide but is not the only circulating variant [5]. Some authors initially postulated that this strain may be more virulent [6]; however, in time, HMPV incidence has not changed significantly [3].…”
Section: Main Textmentioning
confidence: 99%
“…This variant was first described in 2016 and has gradually become the dominating strain worldwide but is not the only circulating variant. 5 Some authors initially postulated that this strain may be more virulent; 6 however, in time, HMPV incidence has not changed significantly. 3 The cause of the unusual summer outbreak of HMPV infections is likely related to reopening of the society after a severe COVID-19 lockdown, thus enabling the spread of HMPV.…”
mentioning
confidence: 99%
“…In 2006, Huck et al first described two distinct clades of A2 viruses, termed A2a and A2b [ 4 ]. Since then, A2b viruses have been shown to cluster in two main clades which have been referred to by different names: A2b1, the clade which includes older sequences and continues to be referred to as A2b by many authors and more recently as A2.2.1; and A2b2, the clade which encompasses most recently isolated viruses, including viruses with partial duplications of the G gene, which is referred to as A2c by many authors, but also referred to as Novel A2 sublineage/Unique A2 sublineage/Unique A2b sublineage and more recently A2.2.2 [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Of interest, in 2017 HMPV strains with partial duplication of the G gene were described [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%